2015
DOI: 10.1155/2015/326184
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Purposeful Use of Forepaws in Female Mice Modelling Rett Syndrome

Abstract: Rett syndrome (RTT) is a rare neurodevelopmental disorder, characterized by severe behavioural and physiological symptoms. Mutations in the methyl CpG binding protein 2 gene (MECP2) cause more than 95% of classic cases. Motor abnormalities represent a significant part of the spectrum of RTT symptoms. In the present study we investigated motor coordination and fine motor skill domains in MeCP2-308 female mice, a validated RTT model. This was complemented by the in vivo magnetic resonance spectroscopy (MRS) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Overall, Mecp2 rats had a signi cant impairment in skilled motor function compared to WT controls. In the current study, the reduced forelimb movement speed, as assessed by longer latencies between presses on the task, are consistent with de cits in motor performance in Mecp2 rats (De Filippis et al, 2015;Veeraragavan et al, 2015). Additionally, Mecp2 rats initiated fewer trials during behavioral testing sessions, consistent with motor hypoactivity previously documented with the open eld and rotarod tasks (Bhattacherjee et al, 2017;Guy et al, 2001;Patterson et al, 2016;Samaco et al, 2013;Stearns et al, 2007;Veeraragavan et al, 2015;Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, Mecp2 rats had a signi cant impairment in skilled motor function compared to WT controls. In the current study, the reduced forelimb movement speed, as assessed by longer latencies between presses on the task, are consistent with de cits in motor performance in Mecp2 rats (De Filippis et al, 2015;Veeraragavan et al, 2015). Additionally, Mecp2 rats initiated fewer trials during behavioral testing sessions, consistent with motor hypoactivity previously documented with the open eld and rotarod tasks (Bhattacherjee et al, 2017;Guy et al, 2001;Patterson et al, 2016;Samaco et al, 2013;Stearns et al, 2007;Veeraragavan et al, 2015;Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, we report a significant increase in Mecp2 ZFN/+  body weight beginning at 2–3 months of age and continuing through development. Several previous mouse studies also report weight gain in heterozygous females (11,13,42,44). …”
Section: Discussionmentioning
confidence: 87%
“…Mecp2 ZFN/+  females demonstrated reduced latency to fall at 9 months of age; however, this difference did emerge after Mecp2 ZFN/+  rats became heavier than WTs, making it difficult to definitively determine a weight-independent effect. Previous studies have reported reductions in latency to fall in heterozygous females as early as PND 30 (22), while others have indicated that motor coordination deficits emerge between 5 weeks and 12 months of age (11,13,22,37,39,42,44,73,74). …”
Section: Discussionmentioning
confidence: 98%
“…Many neurological disorders-ranging widely from cerebrovascular and demyelinating disorders to spinal cord injury, peripheral neuropathies and more-impair dexterous movements, and rodent forelimb tasks have become widely used as translational models to investigate neural mechanisms and therapeutic targets (e.g. [8,37,38]). High-speed close-up video of mice handling food has potential for further development as a quantitative assay to investigate how specific aspects of D1-related manual dexterity relate to neural circuit dysfunction in a wide range of neurological disorders.…”
Section: Discussionmentioning
confidence: 99%